Aromatic annulation with bisphenylthionium ions - Manas, Abdul Rahman; Smith, Robin A. J. (Elsevier, 1987)
The chemospecific production and intramolecular aromatic electrophilic substitution (annulation) of bis(phenylthio)carbocations (bisphenylthionium ions) has been studied using appropriate model compounds. The annulation reaction is very sensitive to the Lewis acid initiator and also the solvent. The best reaction conditions were found to be a suspension of silver trifluoromethanesulfonate in dichloromethane. Annulation of six-membered rings onto alkylbenzenes and five- and seven-membered rings onto activated benzenes have been achieved.